Perioperative complications and risk factors of percutaneous nephrolithotomy - Puttipannee Vorrakitpokatorn (2018)
Objective: To study the risk factors of perioperative complications of PerCutaneous NephroLithotomy (PCNL). Material and Method: The present prospective descriptive study was carried out in the first time operation of 128 PCNL patients after general balanced anesthesia and standard surgical technique. Irrigation fluids were 0.9% NSS (24.1 ± 16.36 liters) at room temperature. Perioperative complications and risk factors were observed, the results were displayed as adjusted Odds Ratio (OR), 95%CI and p value. Results: Intraoperative complications were hypothermia (56.2%), cardiovascular changes (57.1%) and bleeding. The first two complications statistically significantly related to volume of irrigation fluid > 20 liters (7.4, p < 0.05). Postoperative complications were electrolyte changes (but not statistically significant), pleural tear (3 cases), infection and bleeding. Septic shock was found in 4.7% (6/128) and 0.78% (1/128) died. Fever was significantly correlated with postoperative transfusion ≥ 1 unit (adjusted OR 4.9, p < 0.05). Risk factors of postoperative bleeding were operation time (adjusted OR 4.4, p < 0.05), intraoperative transfusion (adjusted OR 10, p < 0.01) and postoperative fever (adjusted OR 4.9 p < 0.01). Mean was 7.3 ± 5.22 days and the mode of Length Of Stay after operation (LOS PO) was 5 days. LOS PO was significantly related with postoperative fever > 38.5°C (adjusted OR 2.7, p < 0.05). Conclusion: Volume of irrigation fluid at room temperature >20 liters significantly increased the rate of intraoperative hypothermia and cardiovascular changes. Infection was the most serious complication of PCNL and increased LOS PO. Antibiotics started at the beginning of the surgery could not always prevent this event.